Structure prediction of the entire proteome of monkeypox variants - Liangzhen Zheng; Jintao Meng; Mingzhi Lin; Rui Lv; Hongxi Cheng; Lixin Zou; Jinyuan Sun; Linxian Li; Ruobing Ren; Sheng Wang (Compuscript Ltd, 2022)
Recently, the monkeypox virus has begun to spread in many countries worldwide [1]. The genome sequence of the monkeypox virus variant responsible for the current outbreak has been reported, thus providing an important resource for better understanding the new variant and accelerating vaccine and drug development. Here, we report structure predictions of the whole proteomes of three monkeypox variants, with annotation of potential small-molecule-binding regions of the proteins. Experimentally determined structures with high similarity to monkeypox proteins were vetted through a structure-alignment algorithm. Our work should help accelerate the development of vaccines and drugs.